189 Evaluation of Hybrid Rye on Growth Performance, Carcass Traits, and Efficiency of Net Energy Utilization in Finishing Steers. (30th November 2020) - Rusche, Warren C; Walker, Julie; Brattain, Rebecca S; Smith, Zachary K
Abstract: Predominately Angus steers (n = 240, initial shrunk BW 404 ± 18.5 kg) were used in a 117d feedlot experiment to evaluate the effect of hybrid rye (KWS Cereals USA, LLC, Champaign, IL; Rye) as a replacement for dry-rolled corn (DRC) on growth performance, carcass traits, and comparative net energy value in diets fed to finishing steers. Rye from a single hybrid (KWS Bono) with an ergot alkaloid concentration of 392 ppb was processed with a roller mill to a processing index (PI) of 78.8 ± 2.29. Four treatments were used in a completely randomized design (n = 6 pens/treatment, 10 steers/pen) where DRC (PI = 86.9 ± 4.19) was replaced by varying proportions of Rye [DRC:Rye, DM Basis (60:0), (40:20), (20:40), and (0:60)]. Liver abscess scores and carcass characteristics were collected at the harvest facility. Carcass-adjusted performance was calculated from HCW/0.625. Performance-adjusted NE was calculated using carcass-adjusted ADG, DMI, and mean equivalent shrunk BW with the comparative NE values for Rye calculated using the replacement technique. Data were analyzed using the GLIMMIX procedure with pen as the experimental unit. Means were separated using linear and quadratic contrasts. Replacing DRC with Rye linearly decreased (P ≤ 0.01) carcass-adjusted final BW, ADG, DMI and G:F. Feeding Rye linearly decreased HCW and LM area (P ≤ 0.04). Distributions of liver scores and USDA grades for quality and yield were unaffected by treatment (P ≥ 0.09). Using observed performance from d 19 to d 117 (period when steers were on final diet), the estimated replacement NEm and NEg values for Rye were 1.93 and 1.26 Mcal/kg, respectively. Rye can be a suitable feed ingredient in finishing diets for feedlot steers with the optimal inclusion in this experiment at 20% of DM. Complete replacement of DRC with Rye depressed DMI, ADG, and G:F.